THE FANTASY GENRE AS AN OBJECT OF LINGUISTIC RESEARCH (British Journal of Global Ecology and Sustainable Development, 2024)
The article examines new formations that abound in works of the genre fantasy, which are of interest to linguistic research. The aim is to determine their specificity within the framework of modern neological theory. The author concludes that they are an element of the virtual world created by the writer’s imagination.